The Influence Of Leadership Style, Motivation, And Remuneration On The Performance Of Public Sector Employees Mediated By Organizational Citizenship Behavior - Muhammad Donal Mon; Irvan Kurniawan; Agustinus Setyawan (Cita Konsultindo Research Center, 2023)
This research aims to evaluate the influence of leadership patterns, motivation, and salary systems on the performance of public sector employees through the mediating role of Organizational Citizenship Behavior (OCB). The research results show that the type of leadership, level of motivation, and level of compensation provided have a positive and significant impact on employee productivity. OCB also acts as a link between these factors and employee performance. This research makes an important contribution to the development of strategies and policies to improve the performance of public sector employees. In addition, this research highlights that effective leadership, high motivation, and an adequate salary system can increase employee productivity. The implications of these findings have significance in efforts to develop strategic steps and policies to increase employee productivity in the public sector.